2016
DOI: 10.1016/j.jtcvs.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the valve reimplantation technique using a graft with sinuses

Abstract: The majority of patients who had their valve reimplanted in a graft with sinuses continue to perform well after 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 30 publications
9
44
0
Order By: Relevance
“…Over the years, several modifications have been developed for the David procedure [13]. Dacron grafts with aortic sinuses have been proposed to better mimic the natural aortic root sinuses [14]. However, we have continued to follow the original David technique [2,13] with a cylindrical tube graft [4,5].…”
Section: Commentmentioning
confidence: 99%
“…Over the years, several modifications have been developed for the David procedure [13]. Dacron grafts with aortic sinuses have been proposed to better mimic the natural aortic root sinuses [14]. However, we have continued to follow the original David technique [2,13] with a cylindrical tube graft [4,5].…”
Section: Commentmentioning
confidence: 99%
“…The longest reported followup with the VG is 13 years, with freedom from reoperation of 90.1 AE 4.3%; for the SG, follow-up out to 20 years with 96.9 AE 1.3% freedom from reoperation is reported. 14,15 Other studies using the VG with long-term follow-up, including a multi-institutional, multisurgeon trial, reported freedom from reoperation between 89% and 94% at 4 years. [16][17][18][19] Because of various modifications of the David procedure using SGs (with or without plication, necking graft down, etc) or switching to the VG midway through the study period, it is difficult to compare isolated repairs using unmodified SGs versus those with neosinuses added because these are typically grouped together in the same category of reimplantation (vs remodeling, which most of these studies sought to compare).…”
mentioning
confidence: 99%
“…The use of commercially available grafts with aortic sinuses presents a technical difficulty because their sinuses are spherical and will deform the aortoventricular junction and the height of the sinuses may not coincide with height of the native aortic valve commissures. De Paulis et al published the results of aortic reimplantation with the Gelweave Valsalva, (Vascutek), with approximately 10% reoperations and 13% moderate or severe AR at 10 years. A study using four‐dimensional magnetic resonance imaging in patients who underwent aortic reimplantation with these types of Valsalva grafts showed normal flows and transvalvular pressure gradients .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless as described by differents authors, 20,27,29 we believe that for valve sparing procedures, it is most important to mantain an optimal geometry of the aortic cusps, coaptation height, and coaptation length.…”
Section: Univariate Analysis Of Clinical and Echocardiographic Variablesmentioning
confidence: 95%